PENERAPAN PRINSIP GOOD GOVERNANCE PADA KANTOR BAGIAN ADMINISTRASI PEMERINTAHAN DAN OTONOMI DAERAH PEMERINTAH KOTA SURABAYA - Ahmad Salman Al Farisi; Teguh Santoso; Endang Indartuti (COMMUNITY OF RESEARCH LABORATORY SURABAYA)
The city of Surabaya itself has received an award as a city that has implemented good governance at the world level. However, the facts in the field are still found some principles of good governance that have not been applied, therefore it is necessary to conduct research on the application of good governance in central agencies in the city of Surabaya. In this study, the object chosen was the Government Administration and Regional Autonomy Section, because this agency is a central part of the process of governance and autonomy in the city of Surabaya. This type of research is qualitative, which from this research shows that there are 2 principles that are not implemented properly there, namely transparency and efficiency, limited access to information to the public because only the SITOMAS application can be accessed by the public. Then for efficiency, sometimes many tasks overlap because there are many complaints from the public who come to the BAPOD office even though it is not their job, as a result many tasks are not completed according to the deadline.